Quality of theses for obtaining a medical degree. San Antonio Abad Cusco National University, Perú, 2000-2009 - Mandujano-Romero, Edson (2013)
Introduction: Poor knowledge on research shown by medical students, and the fact that they must complete their pre-graduate theses in a short time period, lead to doubts with respect to the quality of such research projects. Objective: To determine the quality of theses in order to obtain a medical degree in San Antonio Abad Cusco National University (from 2000 to 2009), and to establish if there is any factor influencing this. Materials and Method: This is a descriptive study using a relational model. The universe was 284 theses. The stratified and random simple included 172 theses. Data was retrospectively and cross-sectionally collected using a valid and reliable instrument, so their quality was assessed (methodology compliance and appropriateness), and we also reviewed the year theses were presented, the number of involved investigators, as well as the design and topics covered. We used the chi square test and some of its corrections for the analysis. Results: Theses were graded as excellent (0%), acceptable (20,3%), and non- acceptable (79,7%). We found theses were appropriate (79,7%). Most sections of all theses, except the investigational questions, were considered as 'non-acceptable'. Methodology deficiencies were mostly related with the following factors (pilot studies (92,4%), references (77,9%), measuring instruments (74,4%), study units (68,6%), and variable operationalization (59,3%). No relationships were found when variables were associated, except when comparing theses during the 2008-2009 period with respect to previous years, and some improvement was found (p<0,05). Conclusions: One of every five theses was graded as acceptable, and the formulation of the problem to be investigated was the best developed section. There were improvements in quality of theses during the last two years of the study period.